PEMANFAATAN MODAL SOSIAL DALAM PEMENANGAN CALON ANGGOTA LEGISLATIF PASCA PINDAH DAPIL PADA PEMILU LEGISLATIF KOTA SURABAYA TAHUN 2014 - Romambo Plaituka, Irene Ria; Ali Azhar, Muhammad; Noak, Piers Andreas (Jurnal Nawala Politika; 2018, 2018)
ABSTRACT Social capital has a three main concept which are: trust, interrelation and similiar code of conduct. These three conceptions could be blended in with the character of the political actor. Direct interaction between actor and society create emotional bounding and trusting. The Habitus becoming the fundamental movement of actor’s action angd thought which is combinated disposition as tendency of behaviour and generative clarification scheme in order to be a bases of people’s assessment. The field in this case becoming a battle arena of social capital of actor and Actor’s habitus creator on the election zone 1 with  social interactions. The actor's who competed in political arena is supported by social organization and the ability to adapt with society to fighting for position as the people's representatives. The final result of the social capital contention led Masduki Toba as the aclamation candidate of PKB party of electoral zone 1 which coming from the support of society.   Keywords: Legislative Election, Habitus, Field, and Social Capital